Distribution and impacts of microplastic incorporation within sea ice. (August 2019) - Geilfus, N.-X.; Munson, K.M.; Sousa, J.; Germanov, Y.; Bhugaloo, S.; Babb, D.; Wang, F.
Abstract: Microplastics (plastic particles <5 mm) are an emerging concern in Arctic sea ice with measured concentrations orders of magnitude higher than in surface seawater. However, incorporation of microplastics into sea ice, and their impact on sea ice properties, is unknown. We added microplastic particles in a microcosm experiment to determine microplastic distributions and effects on sea ice properties. Microplastic additions did not affect sea ice growth, but high concentrations of microplastics at the ice surface resulted in high ice salinity and changes in sea ice albedo. Field studies in the Gulf of Bothnia (Baltic Sea) showed sea ice concentration of microplastics from 8 to 41 particles per liter of melted ice, wich were much lower than those found to impact sea ice properties in the microcosm experiments. However, should microplastic concentrations increase, microplastic incorporation in sea ice may impact sea ice albedo. Highlights: Microplastics are concentrated within sea ice compared from underlying seawater. Microplastic within sea ice does not affect the sea ice growth. High microplastics concentration seems to affect sea ice salinity and albedo.